2015
DOI: 10.1007/s12520-014-0225-0
|View full text |Cite
|
Sign up to set email alerts
|

Beeswax remnants, phase and major element chemical composition of the bronze age mould from Gaj Oławski (SW Poland)

Abstract: The recently found metal casting mould from Gaj Oławski (SW Poland) was designed for the production of socketed axes typical for later stages of the Bronze Age in Poland (ca. 1100-900 BC). This unique artefact is a half of a durable, two-piece wedge-shaped mould and measures 17.5× 7.2×4.0 cm. The surface of the mould is covered copper oxides and carbonates, and the remnant of beeswax was found on its inner surface. The metal forming mould consists of cored dendrites of Cu-dominated (Cu >96.5 wt%, up to 2.2 wt%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Advanced chemical analysis of three molds from the Roman era provides important information on barbaric metallurgy. Baron et al (2016) proposed that the presence of compounds related to wax in the mold points to the fact that the mold has never been used for casting [ 7 ]. However, we hypothesize that the remains of wax detected in molds #1 and #2 point to their use for the production of wax models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced chemical analysis of three molds from the Roman era provides important information on barbaric metallurgy. Baron et al (2016) proposed that the presence of compounds related to wax in the mold points to the fact that the mold has never been used for casting [ 7 ]. However, we hypothesize that the remains of wax detected in molds #1 and #2 point to their use for the production of wax models.…”
Section: Resultsmentioning
confidence: 99%
“…Such models could be used as an intermediate stage in the production of final objects, which were produced using lost-wax casting molds [ 25 ]. Note that carbon layers in the internal parts of molds allow the direct casting of metal objects [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible traces of a carbon coating have been identified on the Isleham mould (Coombs 1971, 397–8) and on a bronze mould from France (Mohen 1978, 29). Another from Poland has beeswax residues, argued to be a fixative for a carbon dressing (Baron et al 2015), though this seems unlikely as the wax would tend to cause casting failures. For casting socketed implements, a core would be required.…”
Section: The Use Of Bronze Mouldsmentioning
confidence: 99%
“…Different studies have proposed different dressing materials based on analysis of residues on Bronze Age mould artefacts: for example, one study suggested smoky flame from burning bones based on results from energy dispersive X-ray spectrometry (EDXRF), wet chemistry, Fourier transform infrared spectroscopy (FTIR), and gas chromatography mass spectrometry (GC/MS) from the black residue in a stone axe mould from Portugal [23]; another study proposed the use of beeswax based on results from FTIR and GC/MS from a black residue in a bronze axe mould from Poland [24]; finally, more recently, a blackish residue on the inner face of a Late Bronze Age mould from Portugal has been analysed by FTIR, revealing the use of clay or charcoal [14].…”
Section: Introductionmentioning
confidence: 99%